If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 12x + -13 Reorder the terms: 12 + 3x = 12x + -13 Reorder the terms: 12 + 3x = -13 + 12x Solving 12 + 3x = -13 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 12 + 3x + -12x = -13 + 12x + -12x Combine like terms: 3x + -12x = -9x 12 + -9x = -13 + 12x + -12x Combine like terms: 12x + -12x = 0 12 + -9x = -13 + 0 12 + -9x = -13 Add '-12' to each side of the equation. 12 + -12 + -9x = -13 + -12 Combine like terms: 12 + -12 = 0 0 + -9x = -13 + -12 -9x = -13 + -12 Combine like terms: -13 + -12 = -25 -9x = -25 Divide each side by '-9'. x = 2.777777778 Simplifying x = 2.777777778
| x^2+4=2x+7 | | -(5-3x)-(5-3x)= | | 13+5.5x=3 | | 3(6x+1)=93 | | f(x)=20(1.5)x | | 10(x-5)-2(x-9)=-28 | | -3.2(5d-7)=-17 | | 13u-91=5u | | 3(x+.2)-(2x+.5)=2(x+.3)-.5 | | 70-7x=8-2x | | 0=7x^2-15x-2 | | -3(-8+5x)=54 | | 6x+8-3x=1-12x-13 | | 5(-4x-7)=25 | | 5(x-2)-2(x-3)=3 | | 5x+6=3(2x+1) | | 0=9x^2+20x+4 | | 0.5y-2=0.33y | | 3x-6-2x=2x+12 | | 4x^2-36+80= | | 7x+7=17+6x | | 2/3x-15=45 | | x=105.3+3.78 | | 5x-12=73 | | 3(x+.2)=2(x-.3)+5.2 | | 14x-28=8x+3-10 | | 10a-5+7a-91=4a+20 | | (24x^6y^3)^(1/3) | | 2x-15=10x+3 | | 3x+2y=500 | | 7a-3b+15=0 | | 3a=0.026 |